Chlor(am)ination of iopamidol: Kinetics, pathways and disinfection by-products formation. (October 2017) - Tian, Fu-Xiang; Xu, Bin; Lin, Yi-Li; Hu, Chen-Yan; Zhang, Tian-Yang; Xia, Sheng-Ji; Chu, Wen-Hai; Gao, Nai-Yun
Abstract: The degradation kinetics, pathways and disinfection by-products (DBPs) formation of iopamidol by chlorine and chloramines were investigated in this paper. The chlorination kinetics can be well described by a second-order model. The apparent second-order rate constants of iopamidol chlorination significantly increased with solution pH. The rate constants of iopamidol with HOCl and OCl − were calculated as (1.66 ± 0.09) × 10 −3 M −1 s −1 and (0.45± 0.02) M −1 s −1, respectively. However, the chloramination of iopamidol fitted well with third-order kinetics and the maximum of the apparent rate constant occurred at pH 7. It was inferred that the free chlorine (i.e., HOCl and OCl − ) can react with iopamidol while the combined chlorine species (i.e., NH2 Cl and NHCl2 ) were not reactive with iopamidol. The main intermediates during chlorination or chloramination of iopamidol were identified using ultra performance liquid chromatography - electrospray ionization-mass spectrometry (UPLC-ESI-MS), and the destruction pathways including stepwise deiodination, hydroxylation as well as chlorination were then proposed. The regular and iodinated DBPs formed during chlorination and chloramination of iopamidol were measured. It was found that iodine conversion from iopamidol to toxic iodinated DBPs distinctly increased during chloramination. The results also indicated that although chloramines were much less reactive than chlorine toward iopamidol, they led to the formation of much more toxic iodinated DBPs, especially CHI3 . Highlights: The chlorination kinetics of iopamidol can be described by a second-order model. Iopamidol chlorination significantly increased with solution pH. Iopamidol chloramination fitted third-order model and maximum k o b s N H 2 C l occurred at pH 7. The destruction pathways of iopamidol by chlor(am)ination were proposed. More iodinated DBPs especially CHI3 was formed in chloramination than chlorination.